A rolling horizon optimization framework for the simultaneous energy supply and demand planning in microgrids - Silvente, Javier; Kopanos, Georgios M.; Pistikopoulos, Efstratios N.; Espuña, Antonio (Elsevier, 2015)
This work focuses on the development of optimization-based scheduling strategies for the coordination of microgrids. The main novelty of this work is the simultaneous management of energy production and energy demand within a reactive scheduling approach to deal with the presence of uncertainty associated to production and consumption. Delays in the nominal energy demands are allowed under associated penalty costs to tackle flexible and fluctuating demand profiles. In this study, the basic microgrid structure consists of renewable energy systems (photovoltaic panels, wind turbines) and energy storage units. Consequently, a Mixed Integer Linear Programming (MILP) formulation is presented and used within a rolling horizon scheme that periodically updates input data information.
Keywords: Energy planning; Rolling horizon; Scheduling; Mathematical programming; Microgrid; Demand side management